PERANAN MOTIVASI PIMPINAN DALAM MENINGKATKAN KINERJA APARATUR BIDANG PERPUSTAKAAN DI DESA LIAH BING DINAS PERPUSTAKAAN DAN KEARSIPAN - Dania Astinawati (ADMINISTRASI PUBLIK, 2018)
DANIA ASTINAWATI. Role of Leaders Motivation In Improving Performance Of Library Apparatus In Liah Bing Village Department Of Library And Archives Of Subdistrict. Muara Wahau under the guidance of Mrs. Dra.Hj. Nanik Pujiastuti, M.Si as First Advisor and Dr. Marjoni Rachman M, Si as Supervisor II.The purpose of this study is to determine whether the Motivation Leaders play a positive role against the Apparatus Apparatus In Liah Bing Village Library Service And Archives Sub-District. Muara Wahau. To get the data the authors do the research. The results showed that the Motivation Leaders play a very important role to the apparatus performance, in the sense that the apparatus performance factor in Liah Bing village library and archives service district. Muara Wahau from month to month even from year to year experienced an increasing change. This is followed by the leadership motivation serves as a variable cause.To improve the performance of the apparatus in addition to the motivation factor of the leader then other factors need to get attention so that the performance of apparatus In Liah Bing Village Library Service And Archives Sub-District. Muara Wahau can be improved.